Insights into the Management of Large Carnivores for Profitable Wildlife-Based Land Uses in African Savannas - Funston, Paul J. (Public Library of Science, 2013)
Large African predators, especially lions (Panthera leo) and leopards (Panthera pardus), are financially valuable for ecotourism and trophy hunting operations on land also utilized for the production of other wildlife species for the same purpose. Predation of ungulates used for trophy hunting can create conflict with landholders and trade off thus exists between the value of lions and leopards and their impact on ungulate populations. Therefore productionist and conservation trade-offs are complexly graded and difficult to resolve. We investigated this with a risk-benefit analysis on a large private wildlife production area in Zimbabwe. Our model showed that lions result in substantial financial costs through predation on wild ungulates that may not be offset by profits from hunting them, whereas the returns from trophy hunting of leopards are projected to exceed the costs due to leopard predation. In the absence of additional income derived from photo-tourism the number of lions may need to be managed to minimize their impact. Lions drive important ecological processes, but there is a need to balance ecological and financial imperatives on wildlife ranches, community wildlife lands and other categories of multiple use land used for wildlife production. This will ensure the competitiveness of wildlife based land uses relative to alternatives. Our findings may thus be limited to conservancies, community land-use areas and commercial game ranches, which are expansive in Africa, and should not necessarily applied to areas where biodiversity conservation is the primary objective, even if hunting is allowed there.